Analysis of E. rutaecarpa Alkaloids Constituents In Vitro and In Vivo by UPLC-Q-TOF-MS Combined with Diagnostic Fragment. (30th June 2016) - Yang, Shenshen; Tian, Meng; Yuan, Lei; Deng, Haoyue; Wang, Lei; Li, Aizhu; Hou, Zhiguo; Li, Yubo; Zhang, Yanjun
Abstract : Evodia rutaecarpa (Juss.) Benth. (Rutaceae) dried ripe fruit is used for dispelling colds, soothing liver, and analgesia. Pharmacological research has proved that alkaloids are the main active ingredients of E. rutaecarpa . This study aimed to rapidly classify and identify the alkaloids constituents of E. rutaecarpa by using UPLC-Q-TOF-MS coupled with diagnostic fragments. Furthermore, the effects of the material base of E. rutaecarpa bioactive ingredients in vivo were examined such that the transitional components in the blood of rats intragastrically given E. rutaecarpa were analyzed and identified. In this study, the type of alcohol extraction of E. rutaecarpa and the corresponding blood sample were used for the analysis by UPLC-Q-TOF-MS in positive ion mode. After reviewing much of the literature and collected information on the fragments, we obtained some diagnostic fragments of the alkaloids. Combining the diagnostic fragments with the technology of UPLC-Q-TOF-MS, we identified the compounds of E. rutaecarpa and blood samples and compared the ion fragment information with that of the alkaloids in E. rutaecarpa . A total of 17 alkaloids components and 6 blood components were identified. The proposed method was rapid, accurate, and sensitive. Therefore, this technique can reliably and practically analyze the chemical constituents in traditional Chinese medicine (TCM).